SYSTEMATIC LITERATURE REVIEW: STUDENTS' MATH COMPREHENSION SKILLS IN HANDLING MATH PROBLEMS - Fitri Arianti (PT. Anagata Sembagi Education, 2024)
This study aims to conduct a literature review on students' ability to understand mathematical concepts when solving mathematical problems from primary to tertiary education levels. The method used was Systematic Literature Review (SLR), which reviewed 53 examples of research on students' ability to understand mathematical concepts. The sample consisted of indexed journals published between 2015 and 2022. Data were collected by documenting all articles related to students' understanding of mathematical concepts, including the year of the study, education level, sample size, and type of study. The results showed that in the last eight years, articles highlighting student characteristics and learning styles dominated, while articles on gender differences and learning media tended to be less popular among researchers. The majority of studies were conducted at the junior secondary level with sample sizes generally less than 30.